Bacterial nanocellulose: engineering, production, and applications. Issue 2 (20th December 2021) - R, Reshmy; Philip, Eapen; Thomas, Deepa; Madhavan, Aravind; Sindhu, Raveendran; Binod, Parameswaran; Varjani, Sunita; Awasthi, Mukesh Kumar; Pandey, Ashok
ABSTRACT: Bacterial nanocellulose (BNC) has been emerging as a biomaterial of considerable significance in a number of industrial sectors because of its remarkable physico-chemical and biological characteristics. High capital expenses, manufacturing costs, and a paucity of some well-scalable methods, all of which lead to low BNC output in commercial scale, are major barriers that must be addressed. Advances in production methods, including bioreactor technologies, static intermittent, and semi-continuous fed batch technologies, and innovative outlay substrates, may be able to overcome the challenges to BNC production at the industrial scale. The novelty of this review is that it highlights genetic modification possibilities in BNC production to overcome existing impediments and open up viable routes for large-scale production, suitable for real-world applications. This review focuses on various production routes of BNC, its properties, and applications, especially the major advancement in food, personal care, biomedical and electronic industries.